Conceptual Design of a Small Hybrid Unmanned Aircraft System. (30th May 2017) - Papa, Umberto; Ponte, Salvatore; Del Core, Giuseppe
Abstract : UAS (Unmanned Aircraft System) technologies are today extremely required in various fields of interest, from military to civil (search and rescue, environmental surveillance and monitoring, and entertainment). Besides safety and legislative issues, the main obstacle to civilian applications of UAS systems is the short time of flight (endurance), which depends on the equipped power system (battery pack) and the flight mission (low/high speed or altitude). Long flight duration is fundamental, especially with tasks that require hovering capability (e.g., river flow monitoring, earthquakes, devastated areas, city traffic monitoring, and archeological sites inspection). This work presents the conceptual design of a Hybrid Unmanned Aircraft System (HUAS), merging a commercial off-the-shelf quadrotor and a balloon in order to obtain a good compromise between endurance and weight. The mathematical models for weights estimation and balloon static performance analysis are presented, together with experimental results in different testing scenarios and complex environments, which show 50% improvement of the flight duration.